Doping with Tungsten - Bad for Humans, Great for Tanks - Powell, Daniel (Cranfield University, 2022)
The distribution of energy within an armour system is a fundamental principle. The joining of the hard disruptive outer layer and soft absorbing backing layer is often a source of weakness in armour systems, causing premature failure and thus defeat of the armour. Novel adhesive techniques to join these thin layers together could have a greater impact on the armour performance with minimal additional weight. Doping epoxy with tungsten powder is one such technique that is currently being considered.
Keywords: Ceramic armour'; 'Impedance'; 'Penetration'; 'DSDS21'; 'DSDS21 Poster'; 'Defence Studies'